HUBUNGAN PERCEIVED BENEFIT DAN PERCEIVED BARRIER DENGAN STADIUM KANKER PAYUDARA BERDASARKAN TEORI HEALTH BELIEF MODEL PADA PASIEN YANG BERKUNJUNG DI POSA RSUD Dr. SOETOMO SURABAYA - Wulan Prihantini; Esty Yunitasari; Retnayu Pradanie (Universitas Airlangga, 2019)
Introduction: Breast cancer is the main cause of women death in the world. Based on breast cancer data at POSA RSUD Dr. Soetomo Surabaya during 2010-2013 showed that 34.051 breast cancer women patient have been visited.Methods: The aimed of this study was to analyze the correlation between perceived benefits and perceived barriers with breast cancer stadium based on Health Belief Models in Patient who visited in POSA RSUD dr. Soetomo Surabaya. This research was a descriptive analytic study using a cross-sectional approach. Data were collected using a questionnaire with 49 respondents then analyzed using Spearman Rho Test.Result: The result showed that there was a significant correlation between perceived benefits with breast cancer stadium with p=0.03, while also perceived showed correlation with breast cancer stadium with p=0.028.Conclusion: It can be concluded that perceived benefits and perceived barriers related to breast cancer stadium. A breast cancer patient should look for treatment early to prevent higher morbidity.